Outcome-focused plan discretion for facilitating residential intensification: Exploring the insights and experience of property developers and planners. (October 2021) - Liu, Wen; Beattie, Lee; Haarhoff, Errol
Abstract: Globally, many planning systems demonstrate the coexistence of characteristics that fall between regulatory zoning and underlying discretion. However, few empirical studies have examined how this combination is perceived an exercised, in particular in the practices of property developers. This study explores the role of the policy framework in development activities, the tactics developers adopt in response, and their perceptions and experience of its influence and effectiveness for realising intended outcomes. This is critically examined through scrutinizing the statutory plan in Auckland (the Auckland Unitary Plan), which employs a combination of prescriptive- and discretionary- approaches in addition to a range of activity-based zones, targeted at delivering a greater proportion of medium to higher density housing. The study explores developers and planners' understandings of this policy framework, the influence and effectiveness of the hybrid approach, and how they respond to this approach. The contradictory results reported in this paper question whether hybrid approaches achieve the outcomes anticipated, in particular, developers may not understand or value the stated policy outcomes. Developers perceive the statutory planning instruments as just one consideration, or a tool for assisting in assessing project feasibility. The hybrid policy-outcome-based-approach therefore remains limited in affecting developers' practices towards achieving the intended policy outcomes. Further, our findings highlight the need to consider market actors as diverse in both their views on the plan's discretionary aspects and their approaches and strategies for adapting to this approach. The findings also shed light on the relationship between the plan quality characteristics of the hybrid approach and the realization of desired outcomes. Highlights: Developers may not value or understand land use plan policy framework. Hybrid policy-outcome-based-approach may not achieve the desired outcomes for intensification. The role of plan approach and policy framework in development activities. Influence and effectiveness of hybrid approach on developers and planners' practices. Plan characteristics of the hybrid approach that promote the realization of outcomes.